Foreign Language Teaching in Public Universities in the Americas - Sánchez Murillo, Julio (2018)
This article describes different aspects of foreign language teaching in the public universities of the Americas: historical references, an inventory of the languages offered, their status and the social, cultural, educational, political, and economic factors that determine their presence in these institutions. This study is based on factors such as the weight of languages and linguistic policies and aims to analyze the place that these languages have within the university context.